Captains courageous - Kipling, Rudyard 1865-1936 (Great illustrated classics, 2002)
After being swept overboard from an ocean liner, fifteen-year-old Harvey Cheyne, spoiled son of a millionaire, is rescued by New England fishermen who put him to work on their boat.